Nanopore sequencing of RAGE gene polymorphisms and their association with type 2 diabetes - Chaurasiya, Arvindkumar H.; Khilari, Ajinkya A.; Kazi, Rubina; Jaiswal, Meera R.; Bhoite, Gouri M.; Padwal, Meghana K.; Momin, Abdulrahaman A.; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (ACS Omega, 2023)
The receptor foradvanced glycation end products (RAGE)is a transmembraneprotein that interacts with its ligands, advanced glycation end products(AGEs). AGEs are elevated in diabetes and diabetic complications,leading to increased oxidative stress and activation of pro-inflammatorypathways facilitated by AGE-RAGE signaling. Polymorphisms inthe RAGE gene can potentially affect AGE-RAGEinteraction and its downstream signaling, which plays a crucial rolein the progression of diabetes and its complications. In this study,we used nanopore sequencing for genotyping of RAGE polymorphism and identified a maximum number of 33 polymorphisms,including two previously unreported novel mutations in a cohort ofhealthy, type 2 diabetics without nephropathy and type 2 diabeticswith nephropathy in order to identify associations. Two novel RAGE polymorphisms in the intron 8 and 3 & PRIME;UTR regionat genomic locations 32181834 and 32181132, respectively, were detectedwith a low frequency. For four previously reported polymorphisms,cross-validation by PCR-RFLP showed 99.75% concordance with nanoporesequencing. Analysis of genotype distribution and allele frequenciesrevealed that five single nucleotide polymorphisms, i.e., rs1800625,rs3131300, rs3134940, rs2070600, and rs9391855, were associated withan increased risk for type 2 diabetes.

Autoantibodies against Nε-carboxymethyl lysine and methylglyoxal modified albumin are associated with cardiovascular risk in type 2 diabetes - Patil, Yugendra R.; Tiwari, Shalbha; Momin, Abdulrahaman A.; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (International Journal of Diabetes in Developing Countries, 2025)
{Background Albumin is an abundant plasma protein which gets modified with advanced glycation end products (AGEs) predominantly in diabetic condition. AGE modification induces immune response and autoantibodies are generated which play an important role in disease pathology. Objective This study aimed to illustrate the role of autoantibodies against N epsilon-carboxymethyl lysine (CML) and methylglyoxal (MG) modified albumin in diabetic cardiovascular complications. MethodsType-2 diabetes subjects were enrolled and further grouped into stress test positive or stress test negative based on treadmill stress test (TMT). Autoantibody titer was quantified by ELISA assay for CML-modified albumin (stress test positive
Keywords: AGE; Atherosclerosis; Diabetes; Glycation; Immune response; ROC